Enhancement of oxygen/pressure sensing performance of Eu3+-doped YSZ phosphors via Bi3+ sensitization. Issue 21 (1st November 2022) - Yang, Lixia; Fu, Yating; Cheng, Weilun; Chen, Zhaofeng; Peng, Di; Zhao, Xiaofeng; Kou, Zongde
Abstract: The effects of the incorporation of a Bi 3+ sensitizer on the phosphorescence properties and oxygen partial pressure sensitivity of the Eu 3+ doped yttria stabilized zirconia (YSZ) phosphors were studied using a lifetime-based optical measurement system. Two series of YSZ: Eu phosphors were investigated in this work: Eu0.01 Bi x Y0.07- x Zr0.92 O1.96 substitutional series and Eu0.01 Bi x Y0.07 Zr0.92- x O1.96-0.5 x additive series. The phosphorescence intensity of the additive-series phosphors was enhanced by 47% excited at 405 nm with a Bi 3+ concentration of 2 mol% due to the energy transfer between Bi 3+ and Eu 3+ . In contrast, the phosphorescence intensity of the substitutional-series phosphors decreased as the Bi 3+ concentration increased. The phosphorescence lifetimes for both series phosphors were highly sensitive to oxygen partial pressure at elevated temperatures. With increasing Bi 3+ concentration, the oxygen sensitivities of both series were enhanced initially, which was related to the increment of concentration dependent non-radiative decay via cross-relaxation between Bi 3+ and Eu 3+ . With 1 mol% Bi 3+ doping, the oxygen sensitivity was enhanced by 28% and 12% for substitutional-series and additive-series phosphors, respectively. As the Bi 3+ concentration further increased, the oxygen sensitivities of both series declined, which was attributed to the energy transfer between Bi 3+, the formation of Bi 3+ aggregates as well as the increase of the Eu 3+ site symmetry. The results of this study not only provided valuable references for phosphor thermometry, but also offered new ideas for developing high-temperature non-contact pressure sensors.